Ecosystem-Wide Impacts of Deforestation inMangroves : the Urabá Gulf (Colombian Caribbean) Case Study (2012)
ABSTRACT: Mangroves are ecologically important and extensive in the Neotropics, but they are visibly threatened by selective logging and conversion to pastures in the Southern Caribbean. The objective of this paper was to summarize the impacts of both threats on forest structure, species composition, aboveground biomass and carbon reservoir, species introgressions, and benthic fauna populations by collating past and current data and by using an interdisciplinary approach in the Urab´a Gulf (Colombia) as a case study. Mangroves in the Eastern Coast have been decimated and have produced unskewed tree-diameter (DBH) distributions due to the overexploitation of Rhizophora mangle for poles (DBH range: 7–17 cm) and of Avicennia germinans for planks and pilings (DBH > 40 cm). Selective logging increased the importance value of the light-tolerant whitemangrove Laguncularia racemosa, also increasing biomass and carbon storage in this species, thus offsetting reductions in other species. Introgressions (cryptic ecological degradation) by L. racemosa and Acrostichum aureum (mangrove fern) and low densities of otherwise dominant detritivore snails (Neritina virginea) were observed in periurban basin mangroves. Finally, basin mangroves were more threatened than fringing mangroves due to their proximity to expanding pastures, villages, and a coastal city.